Experimental study on the fine-scale characteristics of a geogrid-gravelly soil reinforcement influence zone - Liu, Jie; Gao, Bin; Du, Haoyuan; Bai, Qiyu; Yang, Haoyuan; Zhong, Bo; Wang, Bin (Frontiers in Earth Science, 2023)
Based on a specially designed visualization pullout system and digital photographic measurement technology, geogrid pullout tests were conducted by varying the top load, geogrid type, coarse grain content, and particle shape. The evolution and distribution of the reinforcement influence zone and the soil particle displacement field were analyzed, and the effects of various factors on the formation speed of the reinforcement influence zone, gradient layer thickness, and fine-scale particle displacement characteristics were discussed. The study shows that the reinforcement influence zone's basic form and particle displacement direction do not change with pullout displacement after it is fully developed. The displacement layers in the influence zone are centered at the reinforced soil interface and are distributed in a diffusion gradient. The thickness of each gradient layer in the upper influence zone is greater than that in the lower influence zone. The greater the normal load is, the smaller the particle displacement and thickness of each gradient layer, and the slower the formation of the reinforcement influence zone. Using high-strength geogrids and geogrids with nodes can increase the upper interface thickness and improve the reinforcement influence zone’s formation speed. Horizontal ribs play a major role in forming the reinforcement influence zone, while longitudinal ribs mainly affect the formation speed. The indirect reinforcement effect of the geogrid on angular gravel soil is better than that on pebble soil. As the coarse grain content in the fill increases from 20% to 30%, the reinforcement influence zone forms faster, and the particle displacement of each gradient layer is smaller. When the coarse grain content increases from 30% to 35%, there is no significant change in the forming rate of the reinforcement influence zone.